Reduction of port storage and demurrage charges through interdepartmental collaboration in a chemical distribution organization - Asinas, Lovielyn Krystel G. (Animo Repository, 2022)
Chemical distribution involves importation and port releasing procedures. If there is delay in processing, shipments would incur port storage and demurrage charges which could be avoided if necessary actions are done. The purpose of this action research is to involve collaborators in constructing issue, planning, taking, and evaluating action. The first cycle focused on the constructed issue of reducing port storage and demurrage charges caused by late arrival of shipping documents. The implemented action plan includes collection of data, creation of importation and port releasing process flow, discussion regarding importance of tracking shipments, creation of online shipment monitoring file, and execution of organizational restructuring. Evaluation showed that there was decrease in storage and demurrage charges per quantity of imported product in July and August. Feedback from some collaborators revealed that there are other factors which we have not considered yet. Thus, the second cycle centered on the issue of identifying other causes of delay in port releasing. The actions planned and taken involved creation of Corrective Action Report (CAR) form, modification of the online shipment monitoring file, and submission of CAR. From the analysis of data, corrective actions were recommended to avoid additional charges. On evaluation stage of the second research cycle, all collaborators agreed on the successful execution of the project plan. Several first, second, and third person inquiries were used throughout the study. Meta-learning was done through reflecting on the content, process, and premise of both the first and second cycles. This IAR paper could be extrapolated to a broader context by employing similar frameworks or interventions to improve business operations and by bridging the gap between theories and practical application. It enables continuous learning and constant reflection of collaborators to bring value to the organization. Keywords: Action Research, Collaboration, Importation, Demurrage, Corrective Action